PENGARUH HARGA TERHADAP KEPUTUSAN PEMBELIAN ONLINE PADA MAHASISWA JAKARTA GLOBAL UNIVERSITY - Rahmawati Ulfah (JAMER : Jurnal Akuntansi Merdeka, 2023)
This research is to determine the influence of price on online purchasing decisions among students of Jakarta Global University and to assess the magnitude of this influence. The research sample consisted of 135 individuals selected from a population of 1000. Data collected for this study were primary data obtained through questionnaires. Based on the conducted tests, the significance level was found to be 5% = 0.374 > 0.361, indicating that the null hypothesis (H0) is rejected, while the alternative hypothesis (Ha) is accepted. This means that the price has an impact on the online purchasing decisions of students at Jakarta Global University.